Aksesibiltas Kelompok Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Dalam Mengakses Sumber Modal - Mardiyono (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
In the year the 1990s through the UPPKS group loan assistance from the venture capital fund Mandiri Foundation is growing very rapidly. The scheme was launched when it was Skim Takesra and Kukesra. By the year 1997, the number of UPPKS groups have approached the amount of 700 thousand groups throughout Indonesia. With the end of the cooperation between the BKKBN with Independent Fund Foundation, the scheme Takesra Kukesra Mandiri has not been renewed. For a few years later there is vacuum venture capital assistance so that in 2003-2004 was started on social assistance or loan capital of the state budget funds. Overview of this study to identify the knowledge of program managers to access capital sources, identify readiness range of capital sources to implement the existing schemes and identify ways to increase access to capital UPPKS group. The design of this research is descriptive qualitative. The informant's method consists of the Field KS, financial institutions, agencies, both public and private capital, field officers and UPPKS group. The technique used in this study is the determination of the informant sample group (sample group). In this study data collection used three techniques, namely: engineering FGD (Focus Group Discussion), in-depth interviews (depth interview) and documentation. The results of this study concluded that (1) Policy and commitment: MOU with BRI and pawnshops in 3 locations are still the way that the mortgage due in accordance with the commitment, (2) the availability of capital, namely the cooperation between the Ministry of cooperatives and SMEs with Bank Rakyat Indonesia (BRI ) through the Business Credit (KUR), and cooperation between the State Owned Enterprises (SOEs) with the banks. (3) Knowledge capital: Lack of socialization provided by financial institutions that have SME programs so that people, in general, do not know the program. (4) Source informant capital: promotion of the dissemination of leaflets and brochures as well as participation in completing activities at key moments such as the exhibition of products with the PKK, product promotion meetings by the Department of Institutions Mojokerto and others. (4) Management UPPKS group: if the source of the capital of the central BKKBN is not there then they will find it hard to obtain capital relief and will seek assistance loans from other financial institutions.